Ancient Structures of West Moana: Observing the Tombs, Mounds and Forts - Enari, Dion; Lemusuifeauaali’i, Elijah (Te Kaharoa, 2021)
This paper will observe three ancient structures of Western Oceania and analyze their social significance and historic impacts on the native civilizations therein, alongside their relationships with each other among Western Moana cultures. Additionally, this paper will focus primarily on the early kingdoms of Tonga, Sāmoa, Wallis and Futuna; exploring the native land structures of the Star Mounds and Pulemelei mound of Sāmoa, Fort Talietumu in ‘Uvea (Wallis) and royal burial tombs of the Tu’i Tonga in Lapaha, Tongatapu. As researchers who have genealogical links to these sights, we tell this story.